SOCIAL ENTREPRENEURSHIP AS AN INCLUSIVE CLUSTER CONCEPT OF SUSTAINABLE DEVELOPMENT OF THE COUNTRY - Andriy Braunagel (Соціальна економіка)
The purpose of writing the article is the systematization of the elements of the cluster concept and directions for the implementation of the process approach in the management of social entrepreneurship, which will contribute to the acceleration of the implementation of the goals of sustainable development in the social economy. The main characteristic features of social entrepreneurship are presented. The theoretical and practical aspects of the formation of a cluster of social entrepreneurship and its influence on the mechanisms of development of the social economy in unstable conditions are studied. The relationship between the components of the cluster system of social entrepreneurship and process management tools to achieve the effectiveness of ideas regarding social impact, effects, values, and benefits is highlighted. The map of the inductive analysis of the narrative interview according to F. Schütze was developed and presented in the identification of the interests and needs of society in the activity of social entrepreneurship to achieve its sustainability and sustainable development. The scientific and practical tools of the process approach in the management of social entrepreneurship have been systematized. The article states that the clustering of social entrepreneurship determines the grouping of social enterprises and various social initiatives from entrepreneurs on the basis of common characteristics and specific features of their activity by territorial feature or context. It was revealed that the activities of the social entrepreneurship cluster are aimed at creating social value, convergence of the activities of the social entrepreneur and the stakeholders of the social enterprise, their market orientation and social innovations. It is noted that the process of social entrepreneurship determines the provision of social interests and needs through innovative and sustainable entrepreneurial approaches through the creation and management of enterprises or initiatives. A pool of tools for the effectiveness of social entrepreneurship has been identified: promising ideas, social innovations, socially responsible practices, and social institutions. The stages of the process map of social entrepreneurship to achieve sustainable development are characterized.